The interconnection between technology and economic through tourism sectors - Alamsyah Agit; Peter John Wanner; Susilawati Muharram; Oktavianty Oktavianty (CV. Austronesia Akademika, 2024)
The purpose of this paper is to examine the significant role that technology plays in the tourism sector, highlighting how it enhances the efficiency, competitiveness, and economic performance of tourism businesses. It explores the impact of technology on improving the tourist experience, marketing, and distribution of tourism products and services, and how its adoption contributes to economic development, job creation, and income generation. This paper employs a qualitative research method, focusing on the analysis of existing literature and case studies to explore the interconnection between technology and the tourism sector. The findings of the paper highlight the pivotal role of technology in transforming the tourism sector. It underscores how technology enhances the efficiency, competitiveness, and economic performance of tourism businesses. Key points include the facilitation of new touristic experiences through advanced technologies like virtual reality, augmented reality, artificial intelligence, and robotics, which not only improve the tourist experience but also contribute to sustainable tourism practices. Novelty of this paper lies in its comprehensive exploration of the multifaceted role of technology in the tourism sector, particularly focusing on how technology not only enhances the efficiency and competitiveness of tourism businesses but also significantly contributes to the overall economic development. It uniquely synthesizes the impacts of advanced technologies like virtual reality, augmented reality, artificial intelligence, and robotics on creating new touristic experiences and promoting sustainable tourism practices.